(untitled) (Informe Científico Tecnológico, 2024)
With the aim of exchanging information on various subjects about radiation protection and designing a site where the members can send and receive information on courses, scientific activities, articles, technical opinions, commentaries and everything that promotes the communication, collaboration and integration, the 15th March 2002 the networking: “Radioproteccion” is created with 11 persons from 11 countries. The number of members had been increased. By the first month it had 117 members and by the end of the year 2002 it had already 179 members, 315 messages were send by then. By December 2007, there were 726 members from 28 countries mainly from Latin America: Argentina, Brasil, Bolivia, Chile, Colombia, Costa Rica, Cuba, Dominican Republic, Ecuador, Guatemala. Honduras, Mexico, Nicaragua, Panama, Paraguay, Peru, Uruguay and Venezuela. There were also members from Austria, Canada, France, Israel, Italy, Portugal, Spain, Sweden, United Kingdom and United States. There have been distributed 2049 messages about Congress, courses and activities on national and international radiation protection and related issues which initially were in Latin American and the Caribbean. This has allowed diverse specialists that work in different themes to interchange experiences and information about subjects of common interest. This objective is the continuation of the spreading of activities that since 1991 and for 10 consecutive years had been made through the Bulletin "Protección Radiológica", from which 65000 samples were published and distributed to specialists from 40 countries thanks to the support of the International Atomic Energy Agency (IAEA) and the Pan-American Health Organization (PAHO). This idea is complemented by the Web: www.radioproteccion.org. Interesting topics have been discussed in the network for example: Pregnancy and medical radiation, emergency response, occupational exposure, radiation protection responsibilities, lessons learned from accidental exposures, aspects of safety culture, orphan sources, diagnosis and treatment of damage radiation, Radiation Protection Day, regulations, etc. Today the network is consolidating. There is a permanent communication which is an open channel for a great exchange of experiences, papers, publications, articles, events, etc. and to help to solve technical problems.